PENGARUH MOTIVASI, PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA DAN KINERJA PERAWAT DI RUMAH SAKIT dr. SOEBANDI JEMBER - Evanda, Raditya Bagus (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2017)
Abstract : Nurse of dr. Soebandi Hospital as duty bearers geared towards improving the quality of human resources, and the result will have an impact on job performance. Job performance a good nurses is a desirable thing in every hospital, due to the good performance, the hospital will achieve the goals effectively and efficiently. The determining factor to improve achievement nurses is satisfaction of work and motivation. In this research, the population was all the nurse civil servants in dr. Soebandi Hospital Jember, some 194 people from each strata is taken proportionately sample size with the total sample who was elected 131 nurses with a leeway 5 % using Slovin opinion. The sample collection in this study was conducted using stratified random sampling. To test the instruments used in extracting the data in this research, it is necessary to test the validity and reliability of the instrument with the methods of analysis data normality test, and path analysis. The results of the analysis are: (1) motivation has direct and significant impact on job satisfaction of nurses at dr. Soebandi Hospital, Jember; (2) the career development has direct and significant impact on job satisfaction of nurses at dr. Soebandi Hospital, Jember; (3) motivation has direct and significant impact on the nurses performance at dr. Soebandi Hospital, Jember; (4) the career development has direct and significant impact on the nurses performance at dr. Soebandi Hospital, Jember; (5) The job satisfaction has direct and significant impact on the nurses performance at hospital dr. Soebandi Jember.Keywords: motivation, career development, job satisfaction, Nurses